Students’ Perception on the Integrating of Information and Communication Technology (ICT) - Tristiana, Novita Eka; Rosyida, Elvira (Universitas Islam Negeri Raden Intan Lampung, 2018)
The new trends of the integrating of ICT in English Class used by the researchers in Teaching English as Foreign Language (TEFL) methodology class that enables the students get more experience, knowledge and understanding. This research aims to know whether the students have positive perception on the integrating ICT in TEFL methodology class, describe the students’ attitude in learning TEFL methodology Class through the integration of ICT and get the information on the strengths and weaknesses of the integrating of ICT in TEFL methodology class from the students’ perception. The researchers conducted the research in TEFL Methodology Class. The students involved in this research were the students of fifth semester that consist of 30 students in English Department of STKIP Muhammadiyah Pringsewu Lampung. This research is qualitative research which involves case study. In collecting the data, the researchers used questionnaire, in-dept interview and observation. In getting the validity of the data the triangulation was applied by the researcher. From the research finding, the researchers got the information that the students have positive perception in ICT for TEFL methodology class, the students have positive attitude in learning, and integration of ICT for TEFL brings both strengths and weakness.